Peningkatan Fasilitas Landas Pacu Bandar Udara Fatmawati Soekarno – Bengkulu Untuk Meningkatkan Pelayanan Penerbangan - Ataline Muliasari; M. Herry Purnama (WARTA ARDHIA, 2012)
The improvement of the quality and quantity of airplanes owned by some airlines as well as the increasing number of passengers’ movement have demanded every airport to improve its facilities. Fatmawati Soekarno airport has improved the quality of its runway with the value of Pavement Classification Number (PCN) 45 F/X/C/T. With the increasing Pavement Classification Number (PCN) , it is expected that airports can facilitate Boeing 737-900ER aircraft.The problems in this study is the what figure of Permitted Total Load (Pta) of aircrafts is if the Pavement Classification Number (PCN) value is increased. From the above calculation, it shows that the Permitted Total Load (Pta) that can perform landing in the airport’s runway is 75.655 kg. Meanwhile, the Pavement Classification Number (PCN) value is PCN 45/F/C/X/T and the CAN value of a Boeing 737-900ER aircraft is 51 (max) and 24 (min) for CBR low with the Maximum Take Off Weight of 85.130 kg. Peningkatan kualitas dan kuantitas pesawat yang dimiliki oleh beberapa maskapai penerbangan, serta pertumbuhan jumlah pergerakan penumpang, menuntut setiap bandar udara untuk meningkatkan fasilitasnya. Bandar udara Fatmawati Soekarno telah meningkatkan kualitas fasilitas landas pacu dengan nilai Pavement classification Number (PCN) 45 F/X/C/T. Dengan peningkatan nilai Pavement Classification Number (PCN) tersebut, diharapkan bandar udara ini mampu melayani pesawat tipe 737-900ER.Permasalahan dari penelitian ini adalah berapa nilai beban ijin total (Pta) pesawat bila nilai Pavement Classification Number ditingkatkan. Dari hasil perhitungan diatas terlihat bahwa beban ijin total pesawat (Pta) yang dapat mendarat di runway Bandar udara Fatmawati Soekarno adalah 75.655 kg. Sementara itu, Nilai Pavement Clasification Number (PCN) adalah PCN 45/F/C/X/T, dan nilai ACN dari Pesawat Boeing 737 - 900 ER adalah 51 (max) dan 24 (min) untuk CBR Low, dengan Maksimum Take Off Weight (MTOW) sebesar 85.130 kg.